Reaffirm Our Basic Principles and Rectify Errors - Liwanag, Armando (Kasarinlan: Philippine Journal of Third World Studies; Vol 8 No 1 (1992): A Special Issue on the Philippine Left, 2007)
Excerpt Our basic principles are set forth in the documents of reestablishment such as "Rectify Errors and Rebuild the Party," the Party Constitution, and the Party Program. As proletarian revolutionaries, we must always measure ourselves according to these principles. These principles include 1) the repudiation of modem revisionism and adherence to the following: 2) theory of Marxism-Leninism, 3) class analysis of Philippine society as semi-colonial and semi-feudal, 4) general line of a new democratic revolution, 5) leading role of the working class through the Party, 6) theory of people's war and the strategic line of encircling the cities from the countryside, 7) concept of a united front along the revolutionary class line, 8) democratic centralism, 9) socialist perspective and proletarian internationalism.